2019
DOI: 10.1016/j.neuroscience.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of zinc modulation of olfactory bulb AMPA receptors

Abstract: The alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) subtype of ionotropic glutamate receptors mediates most fast excitatory transmission. Glutamate binding to AMPA receptors (AMPARs) causes most AMPARs to rapidly and completely desensitize, and their desensitization kinetics influence synaptic timing. Thus, factors that alter AMPAR desensitization influence synaptic transmission. Synaptically released zinc is such a factor. Zinc is a neuromodulator with effects on amino acid receptors and synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 90 publications
3
13
0
Order By: Relevance
“…The requirement for the residual higher open probability as seen in the presence of g 2 and g 8 for significant inhibition by Zn 21 could underlie the large variability previously reported in primary neuronal recordings. Inhibition of AMPARs currents has been shown at millimolar concentrations of Zn 21 in hippocampal neurons (Mayer et al, 1989;Blakemore and Trombley, 2019); however, other studies that have shown no significant inhibition or even potentiation. For instance, Pan et al (2011) reported that endogenous Zn 21 did not affect AMPARs at the mossy fiber CA3 synapses.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The requirement for the residual higher open probability as seen in the presence of g 2 and g 8 for significant inhibition by Zn 21 could underlie the large variability previously reported in primary neuronal recordings. Inhibition of AMPARs currents has been shown at millimolar concentrations of Zn 21 in hippocampal neurons (Mayer et al, 1989;Blakemore and Trombley, 2019); however, other studies that have shown no significant inhibition or even potentiation. For instance, Pan et al (2011) reported that endogenous Zn 21 did not affect AMPARs at the mossy fiber CA3 synapses.…”
Section: Discussionmentioning
confidence: 97%
“…In the brain, free "chelatable" Zn 21 has been shown to be present at concentrations of !1 mM in glutamatergic synapses (Frederickson et al, 2000) and coreleased with glutamate during synaptic transmission (Qian and Noebels, 2005). Zn 21 modulates the function of ionotropic glutamate receptors, inhibiting the NMDA subtype of ionotropic glutamate receptors (for review, see Paoletti et al, 2009), and having a variable effect on the AMPA subtype of the ionotropic glutamate receptors (Mayer et al, 1989;Blakemore and Trombley, 2019). The inhibitory role of Zn 21 is best illustrated in studies with KO mice for ZnT3, the zinc transporter involved in maintaining vesicular synaptic Zn 21 , which shows a marked increase in seizures and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 2+ binds to NMDA and AMPA receptors (67, 68) and it is likely that, in addition to affecting DA neurotransmission via binding to DAT, cocaine-induced increases in synaptic Zn 2+ release may also exert direct allosteric interactions at ionotropic glutamate receptors to influence cocaine-dependent glutamate neurotransmission, synaptic plasticity, and behaviors such as cocaine locomotor sensitization and cocaine priming-induced reinstatement of cocaine seeking (45, 46, 65, 69). However, the precise mechanism for how cocaine-induced Zn 2+ release would lead to such effects is complicated by the fact that Zn 2+ can exert bidirectional effects at AMPA receptors (70), it can inhibit both synaptic and extrasynaptic NMDA receptors (68), and finally, that cocaine induces projection- and cell type-specific adaptations in the NAc (71), that not all NAc glutamatergic synapses release Zn 2+ , and that the specific zincergic synapses, and the postsynaptic cells they target in regions such as the NAc have not yet been defined. For all these reasons, the specific effects of cocaine-induced Zn 2+ release on glutamatergic signaling are unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the membrane of postsynaptic neurons, zinc ions can cause a number of excitatory or inhibitory reactions by interacting with different receptors, and the best-known targets are N-methyl-D-aspartate glutamate receptor (NMDAR) [ 107 , 119 ], alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (APMAR) [ 120 , 121 ], or voltage-gated Ca 2+ channels [ 122 , 123 ]. The concentration of zinc ions in the postsynaptic nerve terminals is controlled by the ZnT-1 transporter activity; the expression of this transporter depends on the number of free zinc ions within the cell [ 124 ].…”
Section: Zincmentioning
confidence: 99%